Fabrication and Effect of Sulfonated Poly (Ether Ether Ketone) With Cloisite15aÂ® Nanoclays for Microbial Fuel Cell Application - Mohd Yusof, Abdul Halim; Mohamed Amin, Mohamed Afizal; Ismail, Ahmad Fauzi; Noorul Anam, Mohd; Nik Mahmud, Nik Azmi (International Journal of Sustainable Construction Engineering and Technology, 2013)
Ion exchange membranes have been used in microbial fuel cell (MFC) because it can prevent high oxygen permeability and the migration of substrate instead of protons from one chamber to another. Despite all these advantages the usage of this type of membrane suffers several operational problems such as high dissolve oxygen permeability, adverse deformation and proton conductivity which can affect the MFC performance. In order to overcome this problem, new membrane for microbial fuel cell system was fabricated using sulfonated polyether ether ketone (SPEEK) and Cloisite 15A®. The membranes were characterized based on their electrochemical and physical properties. The characteristics of the SPEEK nanocomposite membranes were then compared with the unmodified SPEEK membrane and the commercially available Nafion117 membrane. Based on the result, SPEEK/Cloisite 15A® contributed high energy generated across the load compare to SPEEK without additive and Nafion 117. The incorporation of Cloisite 15A® improved the water uptake from 56 to 78.2 wt% and reduced the dissolve oxygen permeability of the membrane from 1.5 to 0.7 cm/s but the tensile strength behaviour was reduced from 11.2 to 7.5 MPa.